The importance of isokinetic studies for the diagnosis of tendinopathies of the shoulder - Rostan, A. (1999)
Studies of the muscular dynamics of the shoulder play an important role in the study of the causes of rotator cuff disorders of the shoulder based on an analysis of the contribution of different muscle groups to the tennis serve. Prevention of rotator cuff lesions focuses primarily on avoiding an imbalance between eccentric activity of the external rotators and concentric activity of the internal rotators and shoulder depressors. It is therefore essential to test this balance and to perform movements that resemble the strokes in tennis: rotations for the serve and diagonals for the backhand. The diagonals (60 and 260°/s) are tested first, followed by concentric (60 and 240°/s) and eccentric (90°/s) rotation. Normal values for diagonal measurements are less than 1 Nm/kg for extension/adduction, with a flexion-abduction/extension-adduction ratio between 0.60 and 0.75. No significant difference between the dominant and non-dominant side has been found. The external/internal rotation ratio is between 0.55 and 0.60 in tennis players, with normal values being 0.65 and 0.80. The dominant side is generally stronger. Values for eccentric contraction of the rotators are generally 115 to 125% of the concentric contraction values. The eccentric external rotators are quite strong, because they have to counterbalance the powerful internal rotators. This leads to a normal eccentric/concentric ratio of 1.25 to 1.45. The eccentric external rotation/ concentric internal rotation ratio is very important, because diminution of this ratio certainly plays a role in cuff lesions. Normal values should not be lower than 0.95. The eccentric internal rotation/concentric external rotation ratio should also be considered, because an imbalance here seems to be a factor that favors instability, due to subluxation at the start of acceleration. These imbalances have been found various times in tennis players with shoulder pain. In most cases, correction of the imbalance has led to disappearence of the symptoms. Isokinetic measurements form an important part of the evaluation of rotator cuff tendinitis in tenis players and have therefore been introduced as part of he regular medical examinations of the national teams in Switzerland.